Niche Overlap between Pongo pygmaeus wurmbii and Helarctos malayanus Raffles within Small Scale Habitat in Punggualas Area, Sebangau National Park - Panda, Adventus; Krestina, Widya (Journal of Tropical Life Science, 2021)
The Sebangau National Park is a major stronghold for Bornean Orangutan (Pongo pygmaeus wurmbii) ranging from 6000 – 9000 individuals. In comparison with Bornean Orangutans, very little ecological fieldwork has been conducted to investigate sun bear biology, and there have been no thorough surveys of distribution or population densities. Thus, this study aimed to investigate the basic information on niche overlap between these two endangered species, specifically to quantify their relationship within the small-scale habitat in Punggualas area, SNP. Data was collected and measured during 15 – 21 June 2019; using line transects methods. A total of 6580 m was walked along 8 consecutive transects. Bear and aging sign follow Augeri protocols. A total 18 printed mark-claw and 17 Orangutan nests was measured according to the mentioned methodology.  The relationships between signs use binary logistic regressions (StatPlus for Mac) and PCA model (using R), while interspecific relationships use Co-Occurrence modeling, ESP for Windows. The results showed that there is no difference between bear sign and orangutan nest (c2: 26.249; df :1, p-value : 0.001); While the results on habitat selection between transects is failed to reject the null hypothesis (c2 = 0.29; df :1, p-value : 0.490). The Mann-Whitney U test, also confirmed no distinctive overlap between the Orangutan and the Sun Bear (Z: 0.84; p-value: 0.40). The co-occurrence simulations also revealed significant results (C-Score = 1.00), by means both target animals co-existed in the habitat.  Obviously, the Orangutan and Sun Bear occupy the same habitat. There is no distinctive overlap between them in terms of tree species selection and having a close interrelationship in terms of feeding ground, whereas the fruiting is not available. The only distinctive difference is that the Bear sign was tend hindering waterlogged terrain.